2016
DOI: 10.1051/0004-6361/201527054
|View full text |Cite
|
Sign up to set email alerts
|

Radii, masses, and ages of 18 bright stars using interferometry and new estimations of exoplanetary parameters

Abstract: Context. Accurate stellar parameters are needed in numerous domains of astrophysics. The position of stars on the HertzsprungRussell diagram is an important indication of their structure and evolution, and it helps improve stellar models. Furthermore, the age and mass of stars hosting planets are required elements for studying exoplanetary systems. Aims. We aim at determining accurate parameters of a set of 18 bright exoplanet host and potential host stars from interferometric measurements, photometry, and ste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(104 citation statements)
references
References 67 publications
8
95
1
Order By: Relevance
“…The K-band interferometric data, obtained with the 65 m baseline, are compatible with the stellar photosphere parameters derived by Ligi et al (2016), and therefore consistent with a nonexcess as shown in Fig. 5.…”
Section: Results Of Circumstellar Excess Levelssupporting
confidence: 87%
“…The K-band interferometric data, obtained with the 65 m baseline, are compatible with the stellar photosphere parameters derived by Ligi et al (2016), and therefore consistent with a nonexcess as shown in Fig. 5.…”
Section: Results Of Circumstellar Excess Levelssupporting
confidence: 87%
“…The study did not provide an estimate of ρ. All 4 stars are on the MS. Ligi et al (2016), using the VEGA optical interferometer at the CHARA array, determined the angular diameter of 18 stars and estimated R with an error of less than 5%. By fitting SEDs taken from the VizieR SED Viewer, they determined the total flux and derived L and T eff .…”
Section: Data Samplementioning
confidence: 99%
“…The first group of accurate stellar radii obtained using interferometry from the VEGA optical interferometer at the CHARA array has been published (Ligi et al 2016) 3. Tens of accurate stellar densities have been confirmed thanks to planetary transits.…”
Section: Introductionmentioning
confidence: 99%
“…Upper limits on the masses of ultra-short period planets, given their proximity to the stellar Roche limit indicate a likely rocky composition (Rappaport et al 2013). Furthermore, several ultra-short period exoplanets have low masses, as characterized via RV spectroscopy, including 55 Cancri e (Ligi et al 2016), CoRoT-7 b (Faria et al 2016), Kepler-10 b (Weiss et al 2016), Kepler-78 b (Pepe et al 2013;Howard et al 2013), K2-106 b (Guenther et al 2017), K2-131 b ), K2-229 b (Santerne et al 2018) and WASP-47 e (Vanderburg et al 2017); all of these planets orbit G or early-K dwarfs. Both 55 Cancri e and WASP-47 e (both in multiplanet systems with close-in Neptune and Jovian-mass planets) are less dense than would be with an Earth-like composition, hinting at a water-rich composition.…”
Section: Ultrashort Period Planetsmentioning
confidence: 99%
“…The resonant configuration of the system is consistent with planet formation further out, followed by migration to their current orbits, all within 0.07 AU of the star. R⊕ (Ligi et al 2016). Its density is consistent with rock although it appears likely that there are some volatiles.…”
Section: Trappist-1mentioning
confidence: 99%